Activation of the Notch signaling pathway in the anterior cingulate cortex is involved in the pathological process of neuropathic pain. Issue 1 (January 2021) - Duan, Haifeng; Shen, Fengyan; Li, Li; Tu, Zhiyi; Chen, Ping; Chen, Pei; Wang, Zhiru; Liang, Weimin; Wang, Yingwei
Abstract : Abstract: Plastic changes in the anterior cingulate cortex (ACC) are critical in pain hypersensitivity caused by peripheral nerves injury. The Notch signaling pathway has been shown to regulate synaptic differentiation and transmission. Therefore, this study was to investigate the function of the Notch signaling pathway in the ACC during nociceptive transmission induced by neuropathic pain. We adopted Western blotting, N-[N-(3, 5-difluorophenacetyl)-l-alanyl]-S-phenylglycine t-butyl ester (DAPT) microinjections, RNA interference targeting Notch1, Hairy and enhancer of split (Hes) 1 or Hes5, electrophysiological recordings, and behavioral tests to verify the link between Notch signaling in ACC and neuropathic pain with adult male Sprague-Dawley rats. Levels of the Notch intracellular domain were increased in ACC on day 7 after chronic constriction injury surgery or spared nerve injury. Meanwhile, the mRNA level of the downstream effector of Notch signaling Hes1 was increased, whereas the level of Hes5 mRNA did not change. Microinjection of DAPT, a γ-secretase (a key enzyme involved in Notch pathway) inhibitor, into ACC significantly reversed neuropathic pain behaviors. Intra-ACC injection of short hairpin RNA-Notch reduced Notch intracellular domain expression and decreased the potentiation of synaptic transmission in the ACC. Moreover, pain perceptions were also alleviated in rats subjected to chronic constriction injury or spared nerve injury. This process was mainly mediated by the downstream effector Hes1, but not Hes5. Based on these results, the activation of the Notch/Hes1 signaling pathway in the ACC participates in the development of neuropathic pain, indicating that the Notch pathway may be a new therapeutic target for treating chronic pain. Abstract : This study reveals interfering Notch signaling pathway of anterior cingulate cortex in early phase prevents neuropathic pain progress by inhibiting the potentiation of synaptic transmission.